The Effect Concentration Plant Extracts Bintaro(CarberaManghas)Against Mortality Hama armyworm (Spodopteralitura) - Sri Purwanti; Sri Hidayati; Nurlina; Mahrus Ali; Amin Rahayu (Faculty of Agriculture, Merdeka University Surabaya, 2021)
This study aims to determine the effect of combined treatment plant extracts bintaro and giving the extract concentration on the mortality of armyworm pests. While the research method used factorial experiments conducted with a completely randomized design (CRD). Treatment Factor I was the Bintaro plant organs extracted consisting of 4 levels consisting of 4 combinations of Bintaro organs and 5 combinations of extract concentrations so that there were 20 combinations and 1 control (without giving the extract) so that a total of 21 treatments were repeated 3 times, a total of 63 units. trial. The experimental unit was using a jar with a height of 6 cm, a diameter of 12.5 cm with 8 instar 1 tails, so it needed 504 instar 1 caterpillars. Caterpillar feed is sunflower leaves that are added / replaced every day. The results showed that there was an insignificant effect of the combination of the treatment of Bintaro plant organ extracts and the concentration of Bintaro plant organ extracts with the mortality rate (%) of armyworms, where observations on days 4, 8, 12 and 16 showed a significant value> 0, 05 with the highest R Square achievement on the 16th day of observation of 0.0675 (6.75%), meaning that only a 6.75% mortality rate (%) of armyworms was affected by the combination of the above treatments. The insignificant effect at all levels of treatment factors was the concentration of Bintaro plant's organ extract (K), but the K5 treatment (12.5% extract concentration) showed a tendency to be better than the K1, K2, K3, and K4 treatments with an R Square value of 0, 418370978 (41.84%) means a number of 41.85% mortality (%) armyworms due to K5 treatment (12.5% extract concentration), the remaining 58.15% due to external factors and insignificant influence at all factor levels treatment of Bintaro plant organ extract (B), but treatment B1 (leaf organ extract) showed a better tendency than treatment B2, B3, and B4 with a significant value of F (0.264002509> 0.05) and R Square of 0.296443348 ( 29.64%).